Analysis of the Work Discipline of the Ground Support Equipment (GSE) Unit at Adi Soemarmo International Airport - Natasya Ardhia Pramesti; Nur Makkie Perdana Kusuma (CV. Rayyan Dwi Bharata, 2023)
Punctuality in the world of aviation is an important point in work. Adi Soemarmo International Airport is one of the busiest airports. In serving aircraft movements, the Ground Support Equipment unit plays an important role in it, so that the unit requires to always carry out work discipline. The discipline carried out by GSE officers is very important in handling the movement of aircraft, vehicles and goods that cross the apron area. This is to minimize errors that occur when in the field. This study aims to determine the factors that influence the work discipline of the Ground Support Equipment unit. In addition, this study also aims to obtain the results of the work discipline of the Ground Support Equipment unit carried out by Apron Movement Control. This research is descriptive using qualitative methods with data collection methods in the form of observation, interviews, and documentation. The data obtained was in the form of interviews with AMC and GSE unit personnel at Adi Soemarmo International Airport as well as documents used to carry out daily activities. The results of this study indicate that the factors of work discipline at Adi Soemarmo International Airport include compensation, leadership, goals and abilities, fairness, supervision. The five factors give different influences. In terms of work results, personnel can get better results with the two units having a good relationship, supported by an office location that is not far away, making it easier to coordinate and communicate. Personnel carry out work discipline properly based on existing SOPs. Existing constraints such as the occurrence of violations can be handled by the unit according to the rules in enforcing sanctions.